Viral-Reactivated Pneumonia during Mechanical Ventilation: Is There Need for Antiviral Treatment? - López-Giraldo, Alejandra; Sialer, Salvador; Esperatti, Mariano; Torres, Antoni (Frontiers in Pharmacology, 2011)
Respiratory viruses are not a common cause of VAP. Herpesviridae (HSV and CMV) are detected frequently in the lower respiratory tract of ventilated patients. HSV is detected between days 7 and 14 of IMV; presence of the virus does not necessarily imply pathogenicity, but the association with adverse clinical outcomes supports the hypothesis of a pathogenic role in a variable percentage of patients. Bronchopneumonitis associated with HSV should be considered in patients with prolonged IMV, reactivation with herpetic mucocutaneous lesions and those belonging to a risk population with burn injuries or acute lung injury. Reactivation of CMV is common in critically ill patients and usually occurs between days 14 and 21 in patients with defined risk factors. The potential pathogenic role of CMV seems clear in patients with acute lung injury and persistent respiratory failure in whom there is no isolation of bacterial agent as a cause of VAP. The best diagnostic test is not defined although lung biopsies should be considered in addition to the usual methods before starting specific treatment. The role of mimivirus is uncertain and is yet to be defined, but the serologic evidence of this new virus in the context of VAP appears to be associated with adverse clinical outcomes.